Design optimisation of cyber‐physical distributed systems using IEEE time‐sensitive networks. Issue 1 (1st December 2016) - Pop, Paul; Raagaard, Michael Lander; Craciunas, Silviu S.; Steiner, Wilfried
Abstract : In this study the authors are interested in safety‐critical real‐time applications implemented on distributed architectures supporting the time‐sensitive networking (TSN) standard. The on‐going standardisation of TSN is an IEEE effort to bring deterministic real‐time capabilities into the IEEE 802.1 Ethernet standard supporting safety‐critical systems and guaranteed quality‐of‐service. TSN will support time‐triggered (TT) communication based on schedule tables, audio‐video‐bridging (AVB) flows with bounded end‐to‐end latency as well as best‐effort messages. The authors first present a survey of research related to the optimisation of distributed cyber‐physical systems using real‐time Ethernet for communication. Then, the authors formulate two novel optimisation problems related to the scheduling and routing of TT and AVB traffic in TSN. Thus, the authors consider that they know the topology of the network as well as the set of TT and AVB flows. The authors are interested to determine the routing of both TT and AVB flows as well as the scheduling of the TT flows such that all frames are schedulable and the AVB worst‐case end‐to‐end delay is minimised. The authors have proposed an integer linear programming formulation for the scheduling problem and a greedy randomised adaptive search procedure‐based heuristic for the routing problem. The proposed approaches have been evaluated using several test cases.